(untitled) (El Hilo de la Fabula, 2023)
From a perspective of renewal, the traditional notion of "intermediary" is studied from a wide range of genres and forms, considering certain writers as actors and exponents of a cultural, poetic and ethical mediation process, leaving aside the symbolic mediation for works of fiction or creation.